New Molecular Tools for Regulation and Improvement of A40926 Glycopeptide Antibiotic Production in Nonomuraea gerenzanensis ATCC 39727 - Yushchuk, Oleksandr; Andreo-Vidal, Andres; Marcone, Giorgia Letizia; Bibb, Mervyn; Marinelli, Flavia; Binda, Elisa (Frontiers in Microbiology, 2020)
Genome sequencing has revealed that Nonomuraea spp. represent a still largely unexplored source of specialized metabolites. Nonomuraea gerenzanensis ATCC 39727 is the most studied representative species since it produces the glycopeptide antibiotic (GPA) A40926 – the precursor of the clinically relevant antibiotic dalbavancin, approved by the FDA in 2014 for the treatment of acute skin infections caused by multi-drug resistant Gram-positive pathogens. The clinical relevance of dalbavancin has prompted increased attention on A40926 biosynthesis and its regulation. In this paper, we investigated how to enhance the genetic toolkit for members of the Nonomuraea genus, which have proved quite recalcitrant to genetic manipulation. By constructing probe-vectors, we tested the activity of eleven promoters (heterologous and native) using the GusA reporter system in N. gerenzanensis and in Nonomuraea coxensis; this latter species is phylogenetically distant from N. gerenzanesis and also possesses the genetic potential to produce A40926 or a very similar GPA. Finally, the strongest constitutive promoter analyzed in this study, aac(3)IVp, was used to overexpress the cluster-situated regulatory genes controlling A40926 biosynthesis (dbv3 and dbv4 from N. gerenzanensis and nocRI from N. coxensis) in N. gerenzanensis, and the growth and productivity of the best performing strains were assessed at bioreactor scale using an industrial production medium. Overexpression of positive pathway-specific regulatory genes resulted in a significant increase in the level of A40926 production in N. gerenzanensis, providing a new knowledge-based approach to strain improvement for this valuable glycopeptide antibiotic.